Impact of Different Cavity Preparation Techniques on Dentin Bond Strength. (Bangladesh Journal of Medical Science, 2025)
Background The durability and effectiveness of dental restorations are greatly affected by the strength of the dentin bond. Adhesion between dentin and restorative materials may be affected by several cavity preparation processes, including conventional, laser, and air abrasion. Examining how various cavity preparation methods affect dentin bond strength is the goal of this research. Materials and Methods The cavity preparation method was determined by randomly assigning 80 removed human molars to one of four groups: conventional rotary (control), laser, air abrasion, or ultrasonic. After the appropriate procedure was used to prepare each tooth, a composite resin substance with a bonding agent was used to repair it. Specimens were tested for microtensile bond strength after being stored in distilled water for 24 hours. Statistical analysis was performed using one-way ANOVA followed by Tukey’s post hoc test, with a significance threshold of p